1969
DOI: 10.12669/pjms.303.4985
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Salivary and Blood Sialic Acid, Lipid Peroxidation and Antioxidative Status in Oral Squamous Cell Carcinoma (OSCC)

Abstract: Objective : Oral squamous cell carcinoma (OSCC) is considered to be a serious life threatening issue for almost two decades. The objective of this study was to evaluate the over production of lipid peroxidation (LPO) byproducts and disturbances in antioxidant defense system in the pathogenesis of oral cancer. Methods : Lipid peroxidation and antioxidant status in OSCC patients were estimated and compared the sensitivity and specificity of circulating biomarkers (MDA, Sialic acid, Catalase, SOD, GSH and Neurami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 0 publications
4
18
2
Order By: Relevance
“…Serum B2M level in the OSCC group was shown to have a statistically significant (p<0.001) increase, and is in line with findings of previous studies, although the mechanism of altered B2M level is not yet clearly understood 21,22,28,29 . Various postulates have been put forth, which include increased cellular activity, cell membrane turnover and cell division in malignancy [30].Our study showed 90.5% sensitivity and 90.5% specificity by ROC analysis, consistent with other studies 23,31 . B2M was also found to have good diagnostic test accuracy measurements, with a Positive Likelihood Ratio of 9.53, Negative Likelihood Ratio of 0.10, Diagnostic Odds Ratio of 95.3 and a Youden Index value of 0.81.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Serum B2M level in the OSCC group was shown to have a statistically significant (p<0.001) increase, and is in line with findings of previous studies, although the mechanism of altered B2M level is not yet clearly understood 21,22,28,29 . Various postulates have been put forth, which include increased cellular activity, cell membrane turnover and cell division in malignancy [30].Our study showed 90.5% sensitivity and 90.5% specificity by ROC analysis, consistent with other studies 23,31 . B2M was also found to have good diagnostic test accuracy measurements, with a Positive Likelihood Ratio of 9.53, Negative Likelihood Ratio of 0.10, Diagnostic Odds Ratio of 95.3 and a Youden Index value of 0.81.…”
Section: Discussionsupporting
confidence: 91%
“…B2M levels have been reported to be significantly increased in individuals exposed to carcinogens, having premalignant conditions, at different stages of oral cancer and histological differentiation, when compared with healthy controls [20][21][22] . However, it has been shown that serum B2M is a superior diagnostic tool when compared to B2M level in saliva for OSCC 23 . Upregulation of B2M expression in tumour tissue has been associated with OSCC progression, invasion and metastasis, while the suppression of B2M expression in in-vitro studies using small interfering RNA (siRNA) has been shown to decrease cell migration and invasion 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, serum TSA is used as tumor marker in different cancers such as colorectal, prostate, and breast cancers (18). Increased serum (11-15) and salivary (10, 12, 14-16) sialic acids levels have also been reported in oral cancer patients. An increased concentration of sialic acids in tumor cells, and its secretion by some of these cells, increases its concentration in the blood or saliva (17, 18).…”
Section: Discussionmentioning
confidence: 98%
“…Different researchers have reported increased serum (11 - 15) and salivary (10, 12, 14-16) sialic acid levels in oral cancer patients. Sialic acids are sugar compounds at the end of oligosaccharide chains of glycoproteins and glycolipids, which play an important role in the development of neoplastic behaviors, as important compounds of cell membranes (17).…”
Section: Introductionmentioning
confidence: 97%
“…Oral squamous cell carcinoma (OSCC) is the most common malignant neoplasm of the oral cavity [52]. OSCC patients indicated that a specific marker of oxidative stress, malondialdehyde (MDA) in saliva, is a better diagnostic tool as compared to MDA in blood [53]. IL-8 levels in saliva were elevated in patients who had experienced tumour diseases [3].…”
Section: Introductionmentioning
confidence: 99%